Psychotherapy of Depression and Dysthymia - Wilkinson, P (John Wiley and Sons, 2010)
Psychotherapy has the potential to address the health, social and inter-personal problems associated with ageing and to help elderly people take an active part in managing depression. The well-described psychological treatments available for the treatment of depressive illness in older people include cognitive behavioural therapies and interpersonal psychotherapy. Evidence for the efficacy of these therapies comes from a limited number of randomised controlled trials, including trials of care management interventions in primary care. However, there is a need for further evaluation of psychotherapy with clinically representative groups of depressed older people, particularly those with severe depression and age-related changes such as cerebrovascular disease and executive dysfunction. There is also scope for the further evaluation of psychological treatments in the prevention of depression in at-risk groups of older people. © 2011 John Wiley and Sons, Ltd.